2018
DOI: 10.18632/oncotarget.26160
|View full text |Cite
|
Sign up to set email alerts
|

3’Ighenhancers hs3b/hs4 are dispensable forMycderegulation in mouse plasmacytomas with T(12;15) translocations

Abstract: Myc-deregulating T(12;15) chromosomal translocations are the hallmark cytogenetic abnormalities of murine plasmacytomas (PCTs). In most PCTs, the immunoglobulin heavy chain (Igh) locus is broken between the Eμ enhancer and the 3’ regulatory region (3’RR), making the latter the major candidate for orchestrating Myc deregulation. To elucidate the role of the Igh3’RR in tumorigenesis, we induced PCTs in Bcl-xL-transgenic mice deficient for the major Igh3’RR enhancer elements, hs3b and hs4 (hs3b-4-/-). Contrary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…7 39RR knock-out models indicate that its deletion affects mature B-cell lymphoma occurrence, highlighting the key role of this IgH cis-regulatory region for lymphoma progression. 34,35,45 Therefore, as previously reported by us and others, 3,35,46 39RR targeting would in theory provide a potential strategy for the treatment of mature B-cell lymphomas. Translocations in B-cell lymphomas induce epigenetic changes, 47 suggesting that epigenetic drugs that target histone acetylation (inhibitors of histone deacetylases) and histone methylation (EZH2 inhibitors) may provide a new strategy to treat several B-cell lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…7 39RR knock-out models indicate that its deletion affects mature B-cell lymphoma occurrence, highlighting the key role of this IgH cis-regulatory region for lymphoma progression. 34,35,45 Therefore, as previously reported by us and others, 3,35,46 39RR targeting would in theory provide a potential strategy for the treatment of mature B-cell lymphomas. Translocations in B-cell lymphomas induce epigenetic changes, 47 suggesting that epigenetic drugs that target histone acetylation (inhibitors of histone deacetylases) and histone methylation (EZH2 inhibitors) may provide a new strategy to treat several B-cell lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 61%
“…At this time, the development of c-myc-induced plasmacytomas in mice bearing a truncated 39RR gave divergent results. 34,35 Insertion of c-myc into the IgH locus displayed an increase in c-myc transcripts in B cells of young mice. In most cell types, c-myc enforces proliferation but also triggers apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 3'RR integrity (for its optimal transcriptional activity) is required for B-cell lymphomas with CSR-associated translocations (57). In another study modeling murine plasmacytomas with T (12,15) translocations, the same hs3b-hs4 deletion of the 3'RR in Bcl-xL transgenic mice was without effect for Myc deregulation and mouse plasmacytoma generation (58). However, total 3'RR deletion in these plasmacytomas lowered Myc expression and cell growth confirming 3'RR involvement for myc deregulation by T (12,15…”
Section: The 3'rr Cis-transcriptional Igh Enhancer and C-myc Deregulamentioning
confidence: 99%
“…Which of them are of key importance for translocated oncogene expression? Kovalchuk et al showed that hs3a and hs1,2 enhancers are important drivers of Myc overexpression in mouse plasmacytomas, while hs3b and hs4 are dispensable [204]. Another study indicated that 3 RR is not obligatory for translocated c-Myc expression in pro-B cell lymphomas, but essential in peripheral B-cell lymphomas [205].…”
Section: Role Of Igh Enhancers In Regulating Oncogene Expression and Malignant Developmentmentioning
confidence: 99%